(untitled) (East West Medical College Journal, 2026)
Background: Autistics spectrum disorder is a generalized term for a group of complex brain disorder. Autistics spectrum disorder can occur due to dysfunction of mitochondria and abnormal brain bioenergetics. Cellular function impairment due to mitochondrial dysfunction may cause cognitive impairment, language deficits and abnormal energy metabolism in autism. Objective: to evaluate biochemical evidence of the mitochondrial dysfunction by measuring blood ammonia, serum lactate, creatinine kinase (CK), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in autistic children. Methods: This case-control study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January, 2013 to December, 2013. For this study a total number of 100 male children with age range 3-8 years were randomly selected, among which 50 were normal children and 50 were diagnosed autistic children. The autistic children were selected from the Parent’s Forum, Directorate Generals of Health Service (DOHS), Mohakhali, Dhaka and normal children were selected from some normal school. Blood ammonia, serum lactate, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine kinase (CK) level were estimated in all children by standard laboratory method. Independent sample‘t’ test was used for statistical analysis as applicable. P value <0.05 was accepted as significant. Result: The mean of all the measured biochemical variables were found significantly higher (p<0.001) in autistic male children in comparison to control. In addition, elevated levels of serum lactate and CK were found in 94% and 32% of autistic children respectively. Conclusion: From the result of this study it can be concluded that mitochondrial dysfunction may occur in children with autistic spectrum disorder. The biochemical abnormality for mitochondrial dysfunction and the severity of the autistic spectrum disorder is directly related. EWMCJ Vol. 14, No. 2, July 2026: 130-134